Foye's principles of medicinal chemistry - Foye, William O; Foye, William O; Lemke, Thomas L; Williams, David A., 1938- (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
This edition places emphasis on patient-focused pharmaceutical care and on the pharmacist as a therapeutic consultant, rather than a chemist. A new disease state management section explains appropriate therapeutic options for asthma, chronic obstructive pulmonary disease, and men's and women's health problems
Principles of drug discovery -- Drug receptors affecting neurotransmission and enzymes as catalytic receptors -- Pharmacodynamic agents -- Disease state management
Includes bibliographical references and indexes
Keywords: Pharmaceutical chemistry; Pharmacology; Chemistry, Pharmaceutical